CONTROL OF CHEMICAL COMPOSITION OF CASTING BRASS IN INGOTS USED FOR MANUFACTURE OF STOP VALVES - A. A. Pivovarchyk; Е. V. Pivovarchyk (Литьë и металлургия, 2017)
The article presents the results of a research of the chemical composition of brass foundry grade LS, supplied by domestic and foreign producers, as well as the chemical composition of brass lead grade LC4C used for the manufacture of stop valves. The research was made with use of optical emission spectrometers of various models and a scanning microscope. It was established that the pig delivered by the domestic producers corresponds to parameters of chemical composition for the pig’s foundry brand LS, while in the pig supplied by foreign producers there were found disparities of the chemical composition of certain basic elements. The results of the studies showed that the pig supplied by all producers, as well as the melt obtained with its use, contain in its composition such harmful impurities as S, Bi and P in the amount of 0.001%, 0.0017% and 0.0045%, respectively, that can lead to a decrease in the technological properties of products. It has been established that the use of ARL 3460 and OBLF-QSW 750 emission spectrometers and the Tescan VEGA II LMU scanning electron microscope makes it possible to obtain practically identical values of the content of the main elements and impurities in pigs of foundry and brass lead grade LC40C in studies on determining the chemical composition of the materials under study.